Diamondoid coating enables disruptive approach for chemical and magnetic imaging with 10nm spatial resolution - Ishiwata, Hitoshi; Acremann, Yves; Scholl, Andreas; Rotenberg, Eli; Hellwig, Olav; Dobisz, Elizabeth; Doran, Andrew; Tkachenko, Boryslav A.; Fokin, Andrey A.; Schreiner, Peter R.; Dahl, Jeremy E. P.; Carlson, Robert M. K.; et al. (My University, 2012)
Diamondoids are unique molecular nano-materials with diamond structure and fascinating properties such as negative electron affinity and short electron mean free paths. A thin layer of diamondoids deposited on a cathode is able to act as an electron monochromator, reducing the energy spread of photo-emitted electrons from a surface. This property can be applied effectively to improve the spatial resolution in x-ray photoemission electron microscopy (X-PEEM), which is limited by chromatic aberration of the electron optics. In this paper, we present X-PEEM measurements reaching the technological relevant spatial resolution of 10?nm without the need of expensive and complex corrective optics. Our results provide a simple approach to image surface chemical and magnetic information at nanometer scales by employing diamondoids.
Keywords: aberrations; coatings; diamond; electron affinity; electron mean free path; monochromators; ddc:530